Wishes and needs of older persons who have experienced a fall: A qualitative study - Ann Sophia Bertelsen; Jesper Ryg; Tahir Masud; Dorthe S. Nielsen (Wiley, 2019)
Abstract Aim The aim of this study was to explore the needs and wishes in everyday life of older persons who have experienced a fall. Design A hermeneutic‐phenomenological design with semi‐structured interviews. Method Interviews were analysed using systematic text condensation. Results Nine patients (5 women, 4 men) were included. The participants were between 67-95 years old. Seven of the nine participants had suffered from recurrent falls. The analysis revealed four themes: "To maintain meaningfulness in everyday life after experiencing a fall", "Contact with professionals can be a prerequisite for feeling well and motivated after a fall", "A need for assistive technology and aids in everyday life" and "Asking for help can be a challenge". Our findings highlight that older‐person‐centred care and treatment are essential to address the complex variations in needs and wishes of older persons who have experienced a fall.